Meat yield and meat quality characteristics of indigenous, Hilly♂×Sonali♀ crossbred and commercial broiler chicken of similar weight at different storage time - Ali, MH; Habib, M; Bhuiyan, MSA; Azad, MAK; Hashem, MA; Ali, MS (Meat Research, 2022)
The experiment was conducted to investigate meat yield and quality characteristics of indigenous, crossbred Hilly♂ × Sonali♀ and commercial broiler chickens at similar live weight. For this purpose male and female indigenous chickens were purchased from local market, while Hilly♂ × Sonali♀ crossbred was reared up to 12 weeks at Bangladesh Agricultural University (BAU) poultry farm. Sexed male and female of Ross 308 broiler chicks were also reared BAU poultry farm up to 30 days. Six male and six female chickens from each of indigenous, Hilly♂  Sonali♀ and commercial broiler were slaughtered, eviscerated and dissected to compare meat yield and meat quality characteristics during 0, 15 and 30 days of storage period at 1000 g (±50 g) body weight. The eviscerated and defeathered carcasses were stored at -18°C for 0, 15 and 30 days .Considering Indigenous, Hilly♂ ×Sonali ♀ and Broiler chickens of both sexes, shank, neck, carcass yield, dressed weight, breast meat weight were significantly (p<0.05) higher in commercial broiler while wing meat and thigh meat were higher in Hilly♂ × Sonali♀ chicken. The dry matter, crude protein were significantly higher in indigenous chicken while cooking loss, ether extract, ash, peroxide value, free fatty acid value and thiobarbituric acid value were found significantly higher in commercial broiler during different storage time in both sexes. The meat yield parameters did not differ significantly among three storage time. However, cooking loss, pH and crude protein decreased, while dry matter, ether extract, ash, peroxide vale, free fatty acid value, thiobarbituric acid value, increased with the increasing of storage time.